2022
DOI: 10.1186/s12903-022-02086-5
|View full text |Cite
|
Sign up to set email alerts
|

Salivary fluoride concentration following toothbrushing with and without rinsing: a randomised controlled trial

Abstract: Background Caries prevalence has declined significantly since the introduction of fluoridated toothpaste. There have been several developments regarding specific active fluoride ingredients but not enough evidence to support one over the other. The purpose of this double-blind randomized controlled trial was to compare salivary fluoride concentrations of different fluoride formulations in the form of toothpaste with and without post-brushing water rinsing in adults. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…Saliva’s buffering capability, the ability of saliva to wash the surface of the tooth, clear bacteria, control purification and mineralization, and saliva’s antibacterial activities and other mechanisms all contribute to its primary role in the health of teeth. 1 , 3 , 12 Several studies have confirmed that knowledge of the functional properties of saliva as well as those of its separate components allows for a better assessment of susceptibility to dental caries. 12 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Saliva’s buffering capability, the ability of saliva to wash the surface of the tooth, clear bacteria, control purification and mineralization, and saliva’s antibacterial activities and other mechanisms all contribute to its primary role in the health of teeth. 1 , 3 , 12 Several studies have confirmed that knowledge of the functional properties of saliva as well as those of its separate components allows for a better assessment of susceptibility to dental caries. 12 …”
Section: Discussionmentioning
confidence: 99%
“…Therefore, a clinical difficulty assessment system for the prevention and management of dental caries was developed based on the diagnosis and classification of dental caries. 1 It is a widespread infectious disease, caused by several factors determined by the dynamic balance between pathological and protective factors. 2 , 3 Those agents cause local destruction of sensitive hard tooth tissues by acidic byproducts of bacterial fermentation of dietary carbohydrates.…”
Section: Introductionmentioning
confidence: 99%
“…Saliva's buffering capability, the ability of saliva to wash the surface of the tooth, clear bacteria, control purification and mineralization, and saliva's antibacterial activities and other mechanisms all contribute to its primary role in the health of teeth. 1,3,12 Several studies have confirmed that knowledge of the functional properties of saliva as well as those of its separate components allows for a better assessment of susceptibility to dental caries. 12 Cytokines play a large role in regulating many aspects of the immune response, so they are useful tools for diagnosing and monitoring the oral cavity along with other factors.…”
Section: Discussionmentioning
confidence: 99%
“…As for toothbrushing methodology, the brushing manner used in this research was based on the recommendation by The Japanese Association for Dental Science (Fluoride Working Group) for adults [64] which modi ed the F toothbrushing technique by Sjögren et al [65], except for the amount of usage. Salivary Fconcentration and F retention after toothbrushing with uoridated dentifrices are affected by several factors in relation to a) salivary ow rates [10,[66][67][68], b) swallowing of saliva [10,67], c) F concentrations and formulations in dentifrices [5][6][7][8][9][10][11][12][46][47][48][49][50][51][52][53][54][60][61][62][63][69][70][71][72][73][74][75], d) amount of dentifrices usage [5,6,8,10,47,65,69,[76][77][78] along with a time required for tooth brushing [10,47,65,69], e) amount of water and frequencies of mouth rinsing…”
Section: Discussionmentioning
confidence: 99%
“…Toda and Featherstone demonstrated that the concentrations of free Fin 1000 ppm F MFP dentifrices diluted with double-deionized water showed only around 30-40 ppm, while 1100 ppm F NaF dentifrices showed around 1000-1100 ppm, respectively [9]. This is one of the reasons why Fconcentration in saliva following toothbrushing with NaF dentifrices showed not only signi cantly higher Fconcentration, but also more prolonged salivary retention than MFP dentifrices [10][11][12]. Thus, it is important for free Fto be supplied to the oral cavity in relatively high concentrations (more than 0.04 ppm F in saliva) over long periods.…”
Section: Introductionmentioning
confidence: 99%